The pre-analytical phase of laboratory medicine - Lippi, Giuseppe (Henry Stewart Talks, 2026)
Pre-analytical phase, Total testing process, Laboratory and diagnostic errors, Blood specimen quality, Financial impact of pre-analytical errors, Sources of pre-analytical variability, Phlebotomy, Hemolysis